G protein-coupled inwardly rectifying potassium channels in dorsal root ganglion neurons - Gao Xiao-fei; Zhang Hai-lin; You Zhen-dong; Lu Chang-lin; He Cheng (Acta Pharmacologica Sinica, 2016)
Aim: G protein-coupled inwardly rectifying potassium channels (GIRK) are important for neuronal signaling and membrane excitability. In the present study, we intend to find whether GIRK channels express functionally in adult rat dorsal root ganglion (DRG) neurons. Methods: We used RT-PCR to detect mRNA for 4 subunits of GIRK in the adult DRG. The whole-cell patch clamp recording was used to confirm GIRK channels functionally expressed. Results: The mRNA for the 4 subunits of GIRK were detected in the adult DRG. GTPγS enhanced inwardly rectifying potassium (K+) currents of the DRG neurons, while Ba2+ inhibited such currents. Furthermore, the GIRK channels were shown to be coupled to the GABAB receptor, a member of the G protein-coupled receptor family, as baclofen increased the inwardly rectifying K+ currents. Conclusion: GIRK channels are expressed and functionally coupled with GABAB receptors in adult rat DRG neurons.